2021
DOI: 10.1002/nau.24836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visceral manipulation associated with pelvic floor muscles training in women with urinary incontinence: A randomized controlled trial

Abstract: Aims: To compare the effects of manual visceral therapy (MVT) associated with pelvic floor muscle training (PFMT) on urinary incontinence (UI) symptoms, vaginal resting pressure, and maximum voluntary contraction of the pelvic floor muscles (PFM). Methods: A double-blinded randomized controlled trial of 5 weeks duration with two active intervention arms: PFMT + MVT and PFMT + manual sham therapy (MST). Participants were women over 18 years of age with complaint or diagnosis of UI symptoms. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…It was shown that the use of visceral therapy and pelvic floor muscle training did not have a positive effect on improving urinary incontinence in women [20].…”
Section: Visceral Therapymentioning
confidence: 98%
“…It was shown that the use of visceral therapy and pelvic floor muscle training did not have a positive effect on improving urinary incontinence in women [20].…”
Section: Visceral Therapymentioning
confidence: 98%
“…The pelvic urogenital diaphragm should also show similar movement characteristics. If the intra-abdominal pressure is disturbed, the viscera will also yield to compression, and their mobility and motility will be disturbed [ 82 ]. According to Andrew Taylor Still, the founder of osteopathy, multiple dysfunctions of the reproductive organs are due to the retention of body fluids.…”
Section: Visceral Therapy and Physical Activitymentioning
confidence: 99%
“…The blood pressure decreases, and the supply with oxygen and nutrients deteriorates significantly [ 54 ]. We cannot rule out external reasons for dysfunctions of the uterus and the reproductive organs, such as surgical treatments that cause intraperitoneal adhesions within scars, which can also result from the inflammation process [ 82 ].…”
Section: Visceral Therapy and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal pressure between the respiratory diaphragm and the urogenital diaphragm can cause urinary incontinence. Randomised double-blind studies carried out among women suffering from urinary incontinence have shown that the groups which had undergone pelvic floor training and visceral therapy recorded significantly better results and improved quality of life [10].…”
Section: Introductionmentioning
confidence: 99%